Comparative analysis of bioactive compounds in different habitat of Centella asiatica (L.) Urban: Application for in vitro clonal propagation of elite ecotype - Subrata Kundu, Sk Moquammel Haque, Biswajit Ghosh (Journal of Applied Pharmaceutical Science, 2015)
Centella asiatica (L.) Urban is a perennial herb with high utility in traditional medicines and pharmaceutical industries. In India the wild populations C. asiatica are overexploited at an unrestrained rate to cope up with its high market demands. The aim of this study was to identify potential chemotype of C. asiatica from different geographical region in India and optimized in vitro micropropagation protocol of the elite ecotype was established for commercial purposes. Five C. asiatica accessions were collected from different geographic locations and their active biological components were analyzed. Among these accessions total phenolic and flavonoid content combined with ascorbic acid was found to be significantly higher in CA-4 compared to other ecotypes. The free radical scavenging activity as well as reducing power of the CA-4 ecotype also corroborate the higher phenolic content. Therefore the elite ecotype CA-4 was selected for in vitro conservation and micropropagation. Shoot-tips explants was inoculated on Murashige and Skoog basal medium with different concentrations and combinations of cytokinins and auxins. Optimum multiplication was achieved on medium containing 6-benzyl-aminopurine (2.0 mg L–1) and indole-3-acetic acid (0.2 mg L–1). In vitro rooting of multiplied individual shoots was achieved on half strength Murashige and Skoog medium supplemented with IBA (1.5 mg L–1), with a maximum of 16.4 ± 0.22 roots. These micropropagated plants were successfully established in soil after hardening with 94.55 % survival rate.
Keywords: Centella asiatica, bioactive compounds, antioxidant potential, micropropagation.